PO097 Variation in olfaction testing and interpretation is problematic in parkinson's disease research. (1st December 2017) - Mousele, Christina; Malek, Naveed; Grosset, Katherine A; Grosset, Donald G
Abstract : Background: Olfactory loss is common in Parkinson's disease (PD), can distinguish PD from other disorders, and may even identify prodromal PD. However, olfaction worsens with ageing, and is poorer in men than women, so clear definitions are required to interpret olfaction test results. Objectives: To collate types of olfaction identification tests used in the assessment of PD, and the definitions for hyposmia that were used. Methods: Published papers with original data using olfaction identification tests in patients with PD, or possible prodromal PD, were categorised according to the methods used. Results: Four main methods of commercially produced olfaction testing were reported. Analysis methods varied as follows: (1) Raw score values (number of items correct/total number of items), sometimes using age/sex matching with controls, or applying age and/or sex as a covariate in statistical analysis; (2) Cut-offs from score values to categorise as normosmic/hyposmic, although different cut-points were applied between some studies; or (3) Values below age- and sex-derived centiles or standard deviations. Conclusions: Significant variations in methods for testing olfaction and defining hyposmia are problematic. However, standardisation of the definition of hyposmia in PD in future studies is feasible, based on a minimum set of age and sex stratification criteria.